The Interplay Between FOXO1 and Non-coding RNAs in Liver Cancer - Abdelbary, Rowan (AUC Knowledge Fountain, 2025)
FOXO1 is a transcription factor which plays a role in organ development and tumorigenesis, where it acts mainly as a tumor suppressor by controlling cell proliferation, cell cycle progression, and programmed cell death via variable mechanisms. In hepatocellular carcinoma (HCC), FOXO1 has been shown to be downregulated in liver tissues, and the lower expression has been correlated with poor prognosis. In natural killer cells, FOXO1 has been shown to regulate cell maturation and thus its activity. Studies show that non-coding RNAs (ncRNAs), including microRNAs (miRNAs) and long non-coding RNAs (lncRNAs) are contributing to the immune response regulation and disease pathogenesis in HCC. Various studies have identified miRNAs as regulators of the cytolytic activity of natural killer (NK) cells against cancers. Thus, the interplay of non-coding RNAs and FOXO1 may have a crucial role in HCC pathogenesis. Accordingly, the focus of our study was to investigate whether non-coding RNAs and FOXO1 regulate one another in a regulatory loop. The objective of our study was to examine non-coding RNAs as upstream regulators of FOXO1and to understand the impact of FOXO1 on downstream non-coding RNAs.